2016
DOI: 10.1177/1971400916631992
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral transfer phenomenon: A functional magnetic resonance imaging pilot study of healthy subjects

Abstract: Our study shows, in a small group of healthy subjects, the modification of the fMRI activation pathway of a motor task performed by the non-dominant hand after intensive exercise performing the same task with the dominant hand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…This result is also consistent with previous transfer literature, where the cerebellum is one of the regions that is more frequently involved across studies (Jung et al, 2019;Lutz, Weidner, Shah, & Jancke, 2001;Matsumura et al, 2004;Obayashi, 2004;Parsons et al, 2005;Seidler & Noll, 2008;Shimizu, Wu, & Knowlton, 2016;Uggetti et al, 2016;Walz et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This result is also consistent with previous transfer literature, where the cerebellum is one of the regions that is more frequently involved across studies (Jung et al, 2019;Lutz, Weidner, Shah, & Jancke, 2001;Matsumura et al, 2004;Obayashi, 2004;Parsons et al, 2005;Seidler & Noll, 2008;Shimizu, Wu, & Knowlton, 2016;Uggetti et al, 2016;Walz et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…During the transfer test, the old models might be used directly (e.g., those related with the movements of the target, because such movements are equivalent in the training and the transfer phases) or to implement new ones that are useful in the new context, for example, to link the control of the eye and the hand (Miall & Jenkinson, ), which may be reflected in cerebellar activations. This result is also consistent with previous transfer literature, where the cerebellum is one of the regions that is more frequently involved across studies (Jung et al, ; Lutz, Weidner, Shah, & Jancke, ; Matsumura et al, ; Obayashi, ; Parsons et al, ; Seidler & Noll, ; Shimizu, Wu, & Knowlton, ; Uggetti et al, ; Walz et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other researchers have demonstrated bilateral transfer using functional magnetic resonance imaging (fMRI). In 2016, Uggetti et al 49 investigated the association of specific brain activation patterns using fMRI with bilateral transfer while completing a nine hole peg test with nondominant hand and dominant hand training and found significant fMRI activation before and after training, particularly in movement control, coordination and working memory areas. In 2007, twenty-five participants were analyzed using fMRI while they performed a visuomotor adaption joystick task to position a cursor in a target circle, which appeared on a screen in one of four locations 50 .…”
Section: Discussionmentioning
confidence: 99%
“…A modified version of the Nine Hole Peg Test (mNHPT)-a quantitative test of upper extremity function [21]-was adopted to assess motor performance. Previous studies have shown that the performance of the standard NHPT strongly depends on frontoparietal network functioning [22] [23]. Moreover, NHPT performance improves with repetition over time [24], denoting the test's suitability as a motor learning endpoint.…”
Section: Motor Trainingmentioning
confidence: 99%